2017
DOI: 10.3389/fpsyg.2017.02183
|View full text |Cite
|
Sign up to set email alerts
|

Transfer of Training from Virtual to Real Baseball Batting

Abstract: The use of virtual environments (VE) for training perceptual-motors skills in sports continues to be a rapidly growing area. However, there is a dearth of research that has examined whether training in sports simulation transfers to the real task. In this study, the transfer of perceptual-motor skills trained in an adaptive baseball batting VE to real baseball performance was investigated. Eighty participants were assigned equally to groups undertaking adaptive hitting training in the VE, extra sessions of bat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
178
0
6

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 127 publications
(193 citation statements)
references
References 25 publications
9
178
0
6
Order By: Relevance
“…Furthermore, it is important to note that we could show significant improvements for the intervention group in phase 1, and these positive effects remained stable about several month. That result is in line with the results of Gray (2017) who also carried out a retention test.…”
Section: Discussion and Future Directionssupporting
confidence: 90%
See 2 more Smart Citations
“…Furthermore, it is important to note that we could show significant improvements for the intervention group in phase 1, and these positive effects remained stable about several month. That result is in line with the results of Gray (2017) who also carried out a retention test.…”
Section: Discussion and Future Directionssupporting
confidence: 90%
“…The present case of ten training sessions with a maximum length of 15 minutes per participant was sufficient to induce benefits. However, we have to mention two limitations of the study: the relatively small sample size of only fifteen athletes and the lack of the transferring the benefits into reality, as it is demanded by Gray (2017). In future studies, we plan to overcome these deficiencies by increasing the number of athletes and by conducting a transfer study, in which athletes have to react additionally to attacks of real athletes in pre-and posttests.…”
Section: Discussion and Future Directionsmentioning
confidence: 99%
See 1 more Smart Citation
“…The term context is critical to this definition, which means that transfer can be conceptualised to occur from the practice intervention or experience context to video simulation and in situ tests or competition contexts (Müller, Vallence, & Winstein, ; Rosalie & Müller, ). For example, Gray () has conceptualised transfer to occur from a baseball batting virtual simulator training context (that included a visual–perceptual–motor response), to improvement across pretest to post‐tests that included in situ real batting performance (visual–perceptual–motor response) and pitch recognition in the virtual simulator (verbal response), as well as to competition statistics contexts after the training phase. This conceptualisation of transfer is important to consider when reviewing the literature on visual and motor contributions to anticipation discussed later.…”
Section: Psychological Theories Of Perceptual–motor Behaviourmentioning
confidence: 99%
“…All groups undertook pretesting and post‐testing on dart throwing accuracy, as well as a video temporal occlusion dart location test that presented pre‐ and post‐dart flight information that required prediction of final landing position of the dart in three separate areas of the dartboard. Both these tests can be considered as transfer contexts from the practice contexts in this study (see Gray, ). The authors reported that the no‐vision motor and visuomotor (motor pattern training) groups improved their anticipation across testing phases to an extent where it was signficiantly more accurate in the post‐test than the visual training and control groups.…”
Section: Behavioural Evidence Of Visual and Motor Contributions To Lementioning
confidence: 99%